Probing the HIV reverse-transcriptase enzyme with novel bifunctional HIV-1 RT inhibitors of the general formula (NRTI)-spacer-(NNRTI) - Mohamed, Ebrahim (Department of Chemistry, 2015)
Includes abstract.